Renewable energies: modeling and optimization of production cost. (October 2017) - El Kafazi, Ismail; Bannari, Rachid; Adiba, El Bouzekri El Idrissi; Nabil, Hmina; Dragicevic, Tomislav
Abstract: In this work, we aim to contribute to the modeling and the optimization of the energy production. In order to minimize the production costs, the quantity of the available green energy in the power system. The model is implemented under the GAMS 24.7.1 environment and was validated by using CPLEX.The presented model can easily combine different sources of energy, by scheduling the resources with high performance and flexibility. This optimization of production cost is applied in a real case, the cost can be reduced by 38% in winter and by 40, 89% in summer.